Evaluasi Kenyamanan Termal Courtyard Fakultas Teknik Universitas Negeri Gorontalo - Rahmayanti, Rahmayanti; Mutmainnah, Nur; Pratiwi, Niniek (Program Studi Teknik Arsitektur, Fakultas Teknik, Universitas Ichsan Gorontalo, 2025)
Thermal comfort is a fundamental parameter in architectural performance, especially in tropical climate regions. This study presents a thermal evaluation an outdoor open courtyard in the Faculty of Engineering, Universitas Negeri Gorontalo. Field measurements were conducted for 60 minutes using air temperature, black-globe radiation temperature, relative humidity, and wind speed as primary indicators. Results show that the courtyard exceeded comfort tolerance: average temperature reached 46 , global radiation >47 , humidity ranged from 32–48 %, and wind speed was near stagnant. The analysis reveals that direct solar exposure, heat-retentive paving, and blocked cross-ventilation due to building mass arrangement are the main contributors to outdoor thermal stress.